Respuesta :
ax+bx−c=0
Step 1: Add c to both sides.
ax+bx−c+c=0+c
ax+bx=c
Step 2: Factor out variable x.
x(a+b)=c
Step 3: Divide both sides by a+b.
x(a+b)a+b=ca+b
x=ca+b
Step 1: Add c to both sides.
ax+bx−c+c=0+c
ax+bx=c
Step 2: Factor out variable x.
x(a+b)=c
Step 3: Divide both sides by a+b.
x(a+b)a+b=ca+b
x=ca+b
x = [tex]\frac{c}{a+b}[/tex]
given ax + bx - c = 0 ( add c to both sides )
ax + bx = c ( take out a common factor of x on the left side )
x(a + b) = c ( divide both sides by (a + b) )
x = [tex]\frac{c}{a+b}[/tex]